CENTRAL ASIA AS A SPACE, POLITY, PEOPLES, AND FATE - TOLIPOV, Farkhod (CENTRAL ASIA AND THE CAUCASUS, 2005)
The study of contemporary Central Asian counters problems of ontology and conceptualization. Not only current scholarly works on Central Asia, especially after 11 September 2001, but also recent post-independence studies of the region lack adequate and strong scientific approaches. The spectrum of incorrect views on Central Asia ranges from assertions about Uzbekistan’s expansionism and hegemonism in the region and a prognosis of the “Balkanization” of Central Asia to rejection of the applicability of the regional integration concept with regard to the five countries of the region on the grounds that their cultures and political systems are too different. What is more, most locals, that is, Central Asians themselves, have been carried away by the perceptional works Western scholars have presented to them and written about them. What is Central Asia? For Westerners it is there, for locals it is here. Is it strictly definable? People have an idea of America, an idea of Europe, an idea of Eurasia, etc. Does anyone have an idea of Central Asia? I cannot help but recall Edward Said’s research. An interesting methodological warning can be found in his Orientalism that as both geographical and cultural entities—to say nothing of historical entities—such locales, regions, geo CENTRAL ASIA AND THE CAUCASUS graphical sectors as “Orient” and “Occident” are man-made. “Therefore, as much as the West itself, the Orient is an idea that has a history and a tradition of thought, imagery, and vocabulary that have given it reality and presence in and for the West.” 1 I believe this kind of contemplation can be applied to Central Asia. It is not an attempt to replace all the lies with the truth, all the myths with real history, and all the conjectures and prejudices with stringent and absolute definitions of Central Asia. It is only an attempt to make up for the insufficiently positive approach to the region from the viewpoint of the historical predisposition of its countries and peoples to integration.